Training for sports speed and agility. An evidenz-based approach - Gamble, P. (Routledge, 2012)
Speed and agility are central to success in a wide range of sports. Training for Sports Speed and Agility is the first evidence-based study of all those aspects of athletic preparation that contribute to the expression of speed and agility during competition.